Tudományos kutatások a Balaton régióban - Horváthné Szigedi, Katalin; Fehér, András; Szabó, Sára; Kutics, Károly (Acta Scientiarum Socialium, 2013)
Scientific research in Balaton Region During the past decades several researches have been published on Lake Balaton Region from the fields of both natural sciences and social sciences. The main objective of this paper is to select and briefly introduce the main researches. Based on these researches we identified certain correlations between the researches of the two disciplines. In addition, our aim was to explore the reasons of the lack of parallelisms between the different studies. Amongst researches of natural sciences we highlighted the studies on water quality and water levels of Lake Balaton, furthermore we summarized the most important researches and studies based on their subjects since the system change in Hungary. The tradition of social researches is much shorter, than the tradition natural researches, it only goes back to a few decades. The comprehensive social and sociologi-cal exploration of Balaton region began in the 1990s. Within the analysis of the social science researches emphasis was placed on the relevant studies of the Lake Balaton Development Council. We discussed the studies of demographic situation and demographic trends, examination of non-profit sector, the analysis of small and medium enterprise sector, the effects of foreign real estate purchases on local population. In addition we examined the social science researches on water supplementation, and explored the effects of the national media on Lake Balaton Region. In the context of Lake Balaton Project the Lake Balaton Featured Holiday Resort, the definition of Lake Balaton Region, and the territorial coverage was presented. In this context, scientific results were analysed to date on Lake Balaton, and it’s regional policy and the problem of regional classification and spacial planning based on the Act XXI of 1996 on regional development and physical planning, and the National Regional Development Concept (NRDC). The problems of developmental opportunities and the difficulties of assessment of tender opportunities were introduced. The programs and concepts that define the directions of environmental, em-ployment, tourism issues were assessed, like the National Regional Development Concept, Balaton Act, the long term development concept of Lake Balaton Featured Holiday Resort and the strategic programs encompassing the 2002–2006 and the 2007–2017 periods. We gained an insight into the objectives of LIFE III. Community Program and the targets of the previous LIFE community program established by the European Union in order to offer support, hence this is the reason of our country’s joining to the program in 2001. Earlier, in 2006 Lake Balaton Project (Lake Balaton Life Project) intended to establish an Integrated Decision Support System, the aim of the development was to achieve sustainable tourism. In addition to the current topics a Project Report was discussed that contained the sociological examinations of Ibolya Bokor, Gábor Dombi, Miklós Oláh and Tamás Retz, it further involved the studies of Gábor Dombi and Tamás Retz on the population and the national and foreign tourists of the Lake Balaton Feautred Holiday Resort. On the basis of the collected natural science researches it can be clearly stated, that they contributed to the improvement of water quality and to the development of Lake Balaton’s ecology. Regarding to the researches of the socio-economic status of Lake Balaton, we have to admit, that they should have started much earlier in order to ground the effective operation of the Lake Balaton Region. It is possible that the lack of sociological and economic research has also contributed to the declining position of the Lake amongst the tourist destinations until today.